The influence of the work environment, work motivation, and work discipline on the performance of Bandung city human resources personnel agency employees - Yosi Josiva; Dedi Supiyadi; Yoyo Sudaryo; Gurawan Dayona Wijaya; Fanji Wijaya; Dadan Abdul Aziz (Jurnal Scientia, 2024)
This research aims to determine the simultaneous or partial influence of the Work Environment,Work Motivation and Work Discipline variables on the Performance of Bandung City Human Resources Personnel Agency employees. In this research, the samples were employees of the Bandung City Human Resources Personnel Agency with a total sample of 33 people. This research uses quantitative methods with random sampling techniques. And the data analysis tool uses the SPSS version 25.0 program. Based on the results of research at the Bandung City Human Resources Personnel Agency, it shows that the work environment, work motivation and work discipline influence employee performance both partially and simultaneously.